PENGARUH BAURAN PEMASARAN (MARKETING MIX) TERHADAP PENGAMBILAN KEPUTUSAN MENGINAP DI THE SUN HOTEL MADIUN - Muhammad Supriyanto; Muhammad Taali (P3I Politeknik Negeri Madiun, 2018)
The purpose of this study was to determine whether the Marketing Mix had a partial or simultaneous effect on Decision Making Stay at The Sun Hotel Madiun. The population in this study were guests who stayed at The Sun Hotel Madiun. he variable of this study is the Marketing Mix variable which consists of products, prices, places, promotions, people, physical evidence, and process. Research methods. The data analysis method used is multiple linear regression analysis and using the t test and F test. Based on the results of multiple linear regression analysis, it was found that the Marketing Mix variable had a significant effect between the variables of Marketing Mix on Decision Making Stay at The Sun Hotel Madiun partially or simultaneously. By using the t test and the F test, it shows that the hypothesis is accepted and supports the previous research, and the estimated value of Adusted R Square is 0.942, which means 94.2 percent.